2020
DOI: 10.1177/0363546520961555
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Anatomy and Intrinsic Gene Expression of Menisci From Young Adults

Abstract: Background: Meniscal vascular supply is an important determinant of its healing potential. It has been reported that only the peripheral 30% of the meniscus is vascularized in cadavers aged 53 to 94 years; however, the vascularity in young patients, in whom meniscal repair is more often performed, is unknown. Purpose: The primary objective was to analyze and measure the microvascular anatomy of the meniscus in adult cadaveric specimens <35 years old. The secondary objective was to assess angiogenic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 34 publications
3
29
1
Order By: Relevance
“…They reported that a perimeniscal capillary plexus originating in the capsular and synovial tissues of the joint supplies the peripheral 10% to 25% of the meniscus. A recent investigation by Crawford et al 7 confirmed these results in a younger age group. The authors used 13 cadaveric knee specimens with a mean age of 28.5 years (range, 22-34 years).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…They reported that a perimeniscal capillary plexus originating in the capsular and synovial tissues of the joint supplies the peripheral 10% to 25% of the meniscus. A recent investigation by Crawford et al 7 confirmed these results in a younger age group. The authors used 13 cadaveric knee specimens with a mean age of 28.5 years (range, 22-34 years).…”
Section: Discussionmentioning
confidence: 75%
“…Fedje-Johnston et al 13 recently reported a higher cell density for the medial compared with the lateral meniscus in a cohort aged 1 month to 11 years. Crawford et al 7 could not detect a difference in vessel penetration between the medial and lateral meniscus. In our study, no differentiation between the medial and lateral meniscus was made.…”
Section: Discussionmentioning
confidence: 89%
“…For example, annulus fibrosus cells exhibit aberrant behavior, including fibrotic phenotypic changes (alphasmooth muscle actin expression) and even apoptosis, following removal of residual strains (Bonnevie et al, 2019). Similarly, transection of tendons (e.g., rotator cuff (Osti et al, 2017)) perpendicular to the aligned axis leads to similar fibrotic and apoptotic behavior (Egerbacher et al, 2008;Maeda et al, 2011;Lundgreen et al, 2013;T. et al, 2020).…”
Section: Disruption Of Circumferential Collagen Networkmentioning
confidence: 99%
“…Thus, the recent push to “save the meniscus” is complicated by the majority of tears occurring in either the red-white or white zones ( Terzidis et al, 2006 ), limiting repair potential with suturing. Further exacerbating this issue is that the posterior horn of the meniscus appears to be most injured ( Mansori et al, 2018 ; Jackson et al, 2019 ), yet exhibits the lowest vascular penetration ( Crawford et al, 2020 ).…”
Section: The Inner Versus Outer Paradigmmentioning
confidence: 99%
“…In this month’s journal, Crawford and colleagues 5 from the Steadman Philippon Research Institute in Vail, Colorado report on similar microvascular analysis of the human meniscus. They note that the Arnoczky and Warren study was performed on cadaveric specimens in the 6th through 10th decades of life, and their purpose was to provide a similar descriptive analysis in specimens aged under 35 years—the population in which a meniscus repair is most performed in clinical practice.…”
mentioning
confidence: 99%